Bean agronomy and on-farm research in Uganda: A review and future research needs - Wortmann, Charles S.; Kisakye, J. (International Center for Tropical Agriculture, 1991)
Results of agronomic research are reviewed and suggestions for further research are given. Research is needed to derive methods that will enable farmers to integrate climbing beans into their current crop production systems. The wide gap between genetic yield potential and actual results on farmers' fields suggest the need for research on the physiology of bean yields. Computarized simulation and expert system models appropriate for research on beans need to be identified, validated, and improved. The involvement of farmers in research planning and criteria for selecting farmers for different research situation needs, farmer information elicitation methods, farmer identification of research problems and solutions, and farmer evaluation of alternative technologies need more research emphases. (AS)